Complex post-traumatic stress symptoms in female adolescents: the role of emotion dysregulation in impairment and trauma exposure after an acute sexual assault. Issue 1 (31st December 2020) - Villalta, Laia; Khadr, Sophie; Chua, Kia-Chong; Kramer, Tami; Clarke, Venetia; Viner, Russell M.; Stringaris, Argyris; Smith, Patrick
ABSTRACT: Background : Adolescents are at high risk of sexual assault compared to any other age group. The pattern of post-traumatic stress symptoms plus life-impairing disturbances in self-organization (emotion dysregulation, negative self-concept and interpersonal problems) is termed Complex Post-Traumatic Stress Disorder (CPTSD). Research about CPTSD after sexual assault in adolescents is limited owing to the challenges associated with assessing this group. This study aims to determine the frequency and structure of CPTSD, and the relationship of emotion dysregulation with impairment and additional trauma exposure among adolescents who have been sexually assaulted. Method : Prospective cohort study of adolescents attending the Sexual Assault Referral Centres serving London over a 2-year period. We conducted cross-sectional analyses (n = 99) on data collected 4–5 months after sexual assault, and Confirmatory Factor Analyses (CFA) and Latent Class Analyses (LCA) to determine the CPTSD profile. CTPSD was defined according to the ICD-11, selecting symptom indicators from the following measures: Strengths and Difficulties Questionnaire (SDQ), Children's Revised Impact of Event Scale (CRIES-13), Short version of the Mood and Feelings Questionnaire (S-MFQ), The Development and Well-Being Assessment (DAWBA). We analysed the association of CPTSD symptom domains with impairment (measured with the SDQ, and the Children's Global Assessment Scale; C-GAS) and with additional trauma exposure. Results : The frequency of ICD-11 PTSD was 59%, and of ICD-11 CPTSD was 40%. CPTSD symptoms showed a strong fit for a correlated 4-factor model, and LCA distinguished a class of participants with high levels of CPTSD symptoms. Emotion dysregulation was associated with impairment in functioning and exposure to trauma beyond other self-organization disturbances and core PTSD symptoms. Conclusions : Disturbances in self-organization are frequent in sexually assaulted adolescents, and emotion dysregulation is associated with impairment and further exposure to trauma. Emotion dysregulation should be considered in preventive and treatment strategies for these vulnerable youth.